SUPERVISION AS MODEL OF PERSONAL AND PROFESSIONAL DEVELOPMENT OF THE SOCIAL WORKERS - Dimitrijoska, Suncica (Ревија за социјална политика/Journal of Social Policy, 2015)
If we take in consideration the complex social problemsconditioned by traditional political, economic and social relations in oursociety in the immediate work with people, there is an evident need forcompetent professionals, social workers. They should respond to therequests and needs of the current social developments that cannot betreated as traditional, bureaucratic actions in the social work. The socialworkers are required to follow the complex changes in the society and inthe same time to fulfill their function of unchangingness in the socialsystem.The actual context of reforms in the system for social protection inthe Republic of Macedonia, and the introduction of numerous innovationsand standards in the structural and functional aspects require developmentof models for intervention.Changes are needed to meet such expectations of the experts, interms of development of practice based on theory and scientific facts. Thecontemporary social work requires development and directingcompetencies, skills, opinions and resolving problems, team work andcooperation focused on the assistance provider. The need for supervision is evident in all systems that work in the area of provision of support topeople and development of their potentials, activation and usingknowledge, and application of skills in practice.The integrative-developmental supervision is a model whichimproves professional competencies, creates job satisfaction, preventsprofessional burnout syndrome and enhances professional efficacythrough the process of integration of theory and practice.